2006
DOI: 10.1109/tns.2006.886214
|View full text |Cite
|
Sign up to set email alerts
|

Single Event-Induced Instability in Linear Voltage Regulators

Abstract: SET-induced oscillations were measured on a stable linear-regulator that uses the LM124 op-amp in its regulation block. Simulations showed that single events act as stimuli that initiate a large-signal oscillation in the LM124 differential amplifier and compensation capacitor path. Laser testing validated the analysis and confirmed that transistors connected to the compensation capacitor are the most vulnerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This structure is that of a typical low dropout voltage regulator [5] and similar structures have been tested under ionizing radiation [6], [7] and single events [2], [7]. In these two papers, LDPs due to peak detector effect were not reported, probably due to the use of very low load resistance values (2.2 Ω).…”
Section: A From Ideal Blocks To Actual Devices 1) Typical Low Drop-omentioning
confidence: 99%
See 1 more Smart Citation
“…This structure is that of a typical low dropout voltage regulator [5] and similar structures have been tested under ionizing radiation [6], [7] and single events [2], [7]. In these two papers, LDPs due to peak detector effect were not reported, probably due to the use of very low load resistance values (2.2 Ω).…”
Section: A From Ideal Blocks To Actual Devices 1) Typical Low Drop-omentioning
confidence: 99%
“…During the following years, other authors confirmed the possibility of this kind of events [2]- [4]. Of particular importance was the work of Zanchi et al [4] who attributed the appearance of LPDs to external devices rather than internal components, i.e., LPDs in a band-gap BiCMOS voltage reference were related to an external capacitor used to stabilize the system and remove high frequency noise.…”
Section: Introductionmentioning
confidence: 95%
“…3 is called Q12 at the datasheet by National Semiconductors [12]. The actual structure has been determined by several authors [7], [8], [10], [19], [20], although there are minor changes among the schematics provided by the different works. In particular, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The internal topology of the LM124 (Fig. 4) has been depicted in several papers [7], [8], [10], [19], [20] although scarce information is provided about the characteristic of the internal transistors. In fact, the typical procedure is separating the individual transistors by means of laser or ion beams and extract the SPICE parameters using a microprobe and specific instrumentation [18].…”
Section: A DC Behavior Of the Output Stagementioning
confidence: 99%
“…The wide range of input voltages and variation in output loading conditions are critical parameters in determining SETs for these devices, but increase the complexity of radiation testing and data evaluation. It has also been reported that in some cases SETs can induce large signal instabilities [10].…”
Section: Introductionmentioning
confidence: 97%